Insecticidal activity of extract oil on controlling maize grain weevils - Adane Adugna Ayalew (Toxicology Research and Application, 2020)
Postharvest losses are known to be one of the serious constraints upon food security among farmers poor resource in Africa. The use of botanical insecticide in pest management during storage against weevils is often encouraged because synthetic insecticides produce multiple side effects on human and environment. In this study, the insecticidal property of methanol, ethanol, and ethyl acetate extracts of Lantana camara leaf oil and powder for controlling maize weevils, Sitophilus zeamais , was studied. Gas chromatography–mass spectrometry and Fourier transform infrared spectroscopy (FTIR) were used to identify the chemical composition and functional group of solvent extract, respectively. Adult weevil repellency and mortality were studied by the effect of oil concentration at 0% (w/w), 2% (w/w), 3% (w/w), 5% (w/w), 7% (w/w), and 10% (w/w). Repellency effect was also conducted at 6, 12, and 24 h. The number of weevil death increased significantly as exposed time was increased. The extracted oil by the three-solvent fraction had direct repellent and toxic effect to the weevil. From all treatment applied, extracted by methanol fraction had showed highest percentage mortality (74%). The lowest mortality rate was observed in ethyl acetate extract (26%) at 2% (w/w) concentration. The effect of leaf powder and extracted oil on repellency and mortality for insects was due to the presence of bioactive and phytochemical molecules such as Phytol, Pyrroline, Paromomycin, Pyrrolizin, and 1-Eicosano. It was concluded that both L. camara leaf powder and extract oil can be used for the protection of stored maize from infestation S. zeamais.